Transient or permanent inhabitants : cultured internal microbiota of Cichlidogyrus thurstonae and Scutogyrus longicornis (Monogenea: Ancyrocephalidae) from Oreochromis sp. - Ong, Zhi-Zhang; Chong, Yeak-Heng; Wong, Wey-Lim (Penerbit Universiti Kebangsaan Malaysia, 2022)
Monogeneans, a class of parasitic platyhelminthes, are usually found on the surface of fish. When it feeds on its host, it harbours bacteria, which can survive in its gut. Occasionally, the monogeneans may cause damages on fish tissue while feeding and may allow secondary infection. The present study aimed to isolate and identify culturable bacteria obtained within the gill monogeneans, Cichlidogyrus thurstonae and Scutogyrus longicornis, and gill surface of the tilapia fish, Oreochromis sp. based on 16S ribosomal RNA gene sequencing. Monogeneans were isolated from the fish gill filaments and surface disinfected using 70% ethanol before squashed aseptically on Luria Bertani (LB) agar to isolate the internal microbiota. A total of five bacteria species, namely Burkholderia sp., En terobacter h o rmaechei, Enterobacter sp., Ochrobactrum intermedium and Pantoea sp., were found within C. thurstonae, whilst a total of eight bacteria species, namely Burkholderia contaminans, Pantoea dispersa, Sphingomonas yabuuchiae, Rhizobium pusense, O. intermedium, Acinetobacter bereziniae, Escherichia hermannii, and Staphylococcus saprophyticus, were found within S. longicornis in which B. contaminans, P. dispersa, and S. yabuuchiae were also found on the surface of the tilapia fish gill filaments. Enterobacter bugandensis and Acinetobacter pittii were found solely on the surface of the gill filaments. These bacteria are also found in the environment and some of them are believed to be pathogenic to fish. We suggest that monogeneans may serve as potential bacteria reservoirs, which facilitate the transmission of bacteria.